An evaluation of risk factors of leprosy and how it affects treatment outcome in a low endemic state of India - Bhatia, Mannat K.; Singh, Ripudaman; Chopra, Dimple (International Journal of Research in Medical Sciences, 2018)
Background: Leprosy is a chronic infectious disease caused by Mycobacterium leprae. India achieved elimination at the national level in 2005. But it still had world’s leprosy burden in 2015 and currently has a prevalence rate of 0.81 per 10,000. The aim of our study was thus to identify the risk factors associated with the development of leprosy and assess their effect on the treatment outcome of the disease, especially in a low endemic state like Punjab. Methods: A retrospective study conducted across Punjab by assessing the medical records of 55 leprosy admissions that were diagnosed, treated, and monitored at a tertiary hospital and those living in leprosy homes, from a time period of 2015 to 2018. Data was analysed using SPSS 25 software and presented in the form of figures and percentages. Results: Maximum number of leprosy patients under study belonged to upper lower socioeconomic class (46.2%) according to The Modified Kuppuswamy Scale. 48.7% of the patients were migrants to the state of Punjab. Overall, 24 patients (61.5%) were successfully treated. 20.5% were relapse cases while 7.7% default and 2.6% failure cases were seen. Conclusions: This study shows the current status of disease in an otherwise low endemic state. Leprosy is associated with a lower socioeconomic status due to lesser access to health services and lower levels of education. The high rate of disease, lower case reporting and treatment outcomes, as compared to the national averages is a cause for alarm thus more health seeking practices need to be encouraged.